Regular arrangement of collecting venules (RAC) as a predictor of the absence of Helicobacter pylori infection with conventional endoscopes in a Latin American population, diagnostic performance by subgroups - Niño Ramírez, Sebastián (2022)
Introduction: The regular arrangement of collecting venules has high value to predict the absence of gastric infection by Helicobacter Pylori, the studies that have validated this finding were carried out with magnification images and digital chromoendoscopy, it is common to perform endoscopies with conventional white light equipment without magnification. Objective: This study aims to validate this finding as a predictor of the absence of H. Pylori infection using endoscopy equipment with conventional white light without magnification. Material and methods: An observational study was carried out identifying the presence of RAC with a conventional endoscope, the determination of Helicobacter pylori was established by histopathology. Sensitivity, specificity, positive predictive value (PPV) and negative predictive values (NPV) were calculated in relation to the presence of RAC and the H. pylori infection status. Results: 241 patients were included, finding a sensitivity of 5%, with a specificity of 89%. The prevalence of H. Pylori decreased with age. Conclusion: This study reports a low sensitivity with a high specificity of the regular distribution of collecting venules to establish the state of infection by H. Pylori. The diagnostic performance was lower than that reported in studies carried out with chromium endoscopy with magnification.